Model Pemberdayaan Kelompok Rentan KDRT Berbasis Need Asssesment dalam Perspektif Hukum (Universitas Negeri Semarang, 2012)
Kelompok rentan KDRT Pesisir Kabupaten Tegal dihadapkan pada ketidakmampuan memenuhi kebutuhan praktis dan strategis sebagai kebutuhan dasar. layak dalam pemberdayaan perempuan dan anak untuk menciptakan keadilan dan kesetaraan gender. Need assssment ini berbasis pada pemenuhan kebutuhan praktis dan strategis anak dan perempuan. Model pemberdayaan yang efektif dengan menggunakan kerjasama secara sinergis antar komponen masyarakat dan pemerintah, organisasi negara untuk memberdayakan mereka. Maka model pemberdayaan yang efektif dan efisien adalah dengan menggunakan pengembangan pendidikan pemberdayaan perempuan berperspektif hukum dengan life skill yang berbasis pada need assesment pada masyarakat miskin, perempuan nelayan, perempuan buruh petani, buruh melati, buruh melonco lombok. Kendala yang dihadapi dalam melakukan pemberdayaan kelompok rentan KDRT anak dan perempuan adalah kendala kemiskinan yang disebabkan oleh kemiskinan struktural dan kemiskinan kultural, serta ketidak mandirian perempuan karena tidak berpendidikan serta masyarakat yang belum secara sinergis melakukan pemberdayan terhadap mereka. Vulnerable groups of domestic violence in the area of Tegal Regency coastal faced inability to meet the practical needs and strategic as basic needs. Feasible within the empowerment of women and children to create justice and gender equality. The need assessment is based on practical and strategic needs of children and women. This research aims to analyze the suitable model of vulnerable groups empowering which is based on their needs. The data used are primary and secondary. The analyze is using qualitative technic. The result of this research shows that effective empowerment model is using a synergistic cooperation between the components of society and government, state organizations to empower them. The model of empowerment that effectively and efficiently used is the educational development of the legal perspective of women’s empowerment with life skill needs assessment based on the poor, women fishers, women’s unions of farmers, laborers jasmine, lombok melonco workers. Constraints faced in empowering vulnerable groups of children of domestic violence and women’s poverty is caused by the constraints of structural poverty and cultural poverty, and lack of female mandirian because people are not educated and do not in synergy towards their empowerment.